Healthy Eating in Low-Income Rural Louisiana Parishes: Formative Research for Future Social Marketing Campaigns - Fergus, Linda (Int J Environ Res Public Health, 2021)
High rates of obesity and chronic disease exist in the southeastern United States (US). Knowledge about the attitudes, beliefs, and barriers of the rural low-income Louisiana population regarding healthy eating is limited. Focus Group discussions based on the Theory of Planned Behavior (TPB) were conducted in rural parishes (N = 3) with low-income residents of Louisiana (N = 29). Grounded Theory methods and cross-case analysis were used. The participants were primarily single Black females of age 18–30 years who earned a high school diploma, were employed, and had children. Beliefs included healthy eating was physically beneficial, yet financial impacts and the low palatability of healthy foods were barriers. Professional resources for nutrition education were limited which led to reliance on friends, family, and the internet. Friends and family were positive and negative influences on eating choices. Control beliefs included the high prices and low palatability of healthy foods, the wide availability of Energy Dense Nutrient Poor (EDNP) foods, and low motivation to sustain eating behavior changes. Formative research to optimize campaign distribution channels may improve accessibility to social marketing support and healthy eating resources. Persuasive messages that address control beliefs are needed in social marketing campaigns for rural low-income Louisiana environments.